A Simple Analytical Method for High-Throughput Screening of Major Sugars from Soybean by Normal-Phase HPLC with Evaporative Light Scattering Detection. (1st July 2015) - Valliyodan, Babu; Shi, Haiying; Nguyen, Henry T.
Abstract : This paper presents a simple analytical method for determining sugars in soybean ( Glycine max (L.) Merr.) tissues. Sample preparation was modified from several early published methods. High-performance liquid chromatography (HPLC) equipped with an evaporative light scattering detector (ELSD) was used to separate, identify, and quantify seven sugars, including glucose, galactose, fructose, sucrose, melibiose, raffinose, and stachyose. Two mobile phases were programed into a gradient elution. Mobile phase A is pure water and mobile phase B is a mixture of acetonitrile and acetone 75 : 25 (v/v). Total chromatographic retention time is less than 20 minutes. This method has been validated for detection limit, calibration range, and intraday and interday repeatability. This method has been used analyzing more than 5000 soybean samples in the experiments studying natural genetic variation of sugar contents and components in soybean seeds and other tissues.